Design of the Fast Algorithm for Discrete Orthogonal Transforms and Their Unified Architectures - HUANG Hai; LIU Hong-yu; XING Lin; NA Ning; LI Chun-bao (Journal of Harbin University of Science and Technology)
Discrete orthogonal transform ( DOT ) is widely used in digital image processing and video compression，and it is of great practical significance to study its fast algorithm and design of general architecture. Because various video compression algorithms are widely proposed，the DOT of specific types and points cannot meet the development requirements in the field of image and video. Therefore，it is an unsolved problem to study a multi-type，arbitrary point DOT fast algorithm and its general architecture. Aiming at the above problems，this paper proposes a fast algorithm based on COＲDIC for DOT and designs a general architecture that can implement multiple orthogonal transform algorithms. The experimental results show that the algorithm has obvious advantages in complexity，scalability，pipeline design and easy VLSI implementation compared with the existing algorithms. The general architecture is simple to calculate and high hardware reuse rate，which can meet the needs of multiple applications compared with the existing architecture.